Regulatory effects of gradient microtopographies on synapse formation and neurite growth in hippocampal neurons. (1st July 2022) - McNaughton, Ryan; Huo, Yuda; Li, Guicai; Di Via Ioschpe, Anais; Yan, Lei; Man, Heng-Ye; Zhang, Xin
Abstract: Among approaches aiming toward functional nervous system restoration, those implementing microfabrication techniques allow the manufacture of platforms with distinct geometry where neurons can develop and be guided to form patterned connections in vitro . The interplay between neuronal development and the microenvironment, shaped by the physical limitations, remains largely unknown. Therefore, it is crucial to have an efficient way to quantify neuronal morphological changes induced by physical or contact guidance of the microenvironment. In this study, we first devise and assess a method to prepare anisotropic, gradient poly(dimethylsiloxane) micro-ridge/groove arrays featuring variable local pattern width. We then demonstrate the ability of this single substrate to simultaneously profile the morphologcial and synaptic connectivity changes of primary cultured hippocampal neurons reacting to variable physical conditons, throughout neurodevelopment, in vitro . The gradient microtopography enhanced adhesion within microgrooves, increasing soma density with decreasing pattern width. Decreasing pattern width also reduced dendritic arborization and increased preferential axon growth. Finally, decreasing pattern geometry inhibited presynaptic puncta architecture. Collectively, a method to examine structural development and connectivity in response to physical stimuli is established, and potentially provides insight into microfabricated geometries which promote neural regeneration and repair.